The mediation of green supply chain management towards sustainable construction in Algeria - Ahmed Harouache, Ahmed Harouache (2022)
The construction industry is an important business sector providing physical equipment and infrastructure through supply and demand patterns that have a strong indirect impact on other industries. This study aims to improve sustainable construction in the construction industry sector in Algeria. Green supply chain management provides general guidelines for analyzing, redesigning, and coordinating the entire supply chain of the building and continuous improvement, solving basic problems, and controlling short-sighted supply chains. The objective of this study is to examine the mediating role of green supply chain management between traditional supply chain management and sustainable construction in the Algerian construction industry. Thirteen hypotheses tailored by the theoretical lenses of the social exchange theory (SET) were proposed to test the theorized relationship of traditional supply chain management (design, manufacturing, distribution, and purchasing), green supply chain management, and sustainable construction. Green Supply Chain Management as a mediator contained five dimensions namely, eco-design, green manufacturing, green distribution, green purchasing, and reverse logistics. A quantitative approach is used to obtain data from a survey (questionnaire) consisting of 61 items with a five-point Likert scale. A total of 237 executives and risk managers in the construction companies of Algeria participated in the study. The data analysis was conducted using Smart PLS. The findings of the path analysis of partial least squares (PLS) support variables in the hypothesized direct and indirect relationships with sustainable construction. The results showed that the relationship between traditional supply chain management and sustainable construction is positive. Mediation of GSCM results showed a positive and significant effect on the relationship between traditional supply chain management and sustainable construction. This study leads future employers, designers, manufacturers, contractors, and suppliers to improve the use of green supply chain management for sustainable construction in Algeria